Human exposure to per- and polyfluoroalkyl substances (PFAS) via the consumption of fish leads to exceedance of safety thresholds - Håkon Austad Langberg; Gijsbert D. Breedveld; Roland Kallenborn; Aasim M. Ali; Sarah Choyke; Carrie A. McDonough; Christopher P. Higgins; Bjørn M. Jenssen; Morten Jartun; Ian Allan; Timo Hamers; Sarah E. Hale (Environment International, 2024)
Per- and polyfluoroalkyl substances (PFAS) receive global attention due to their adverse effects on human health and the environment. Fish consumption is a major source of human PFAS exposure. The aim of this work was to address the lack of harmonization within legislations (in the EU and the USA) and highlight the level of PFAS in fish exposed to pollution from diffuse sources in the context of current safety thresholds. A non-exhaustive literature review was carried out to obtain PFAS concentrations in wild fish from the Norwegian mainland, Svalbard, the Netherlands, the USA, as well as sea regions (North Sea, English Channel, Atlantic Ocean), and farmed fish on the Dutch market. Median sum wet weight concentrations of PFOA, PFNA, PFHxS, and PFOS ranged between 0.1 µg kg−1 (farmed fish) and 22 µg kg−1 (Netherlands eel). Most concentrations fell below the EU environmental quality standard (EQSbiota) for PFOS (9.1 µg kg−1) and would not be defined as polluted in the EU. However, using recent tolerable intake or reference dose values in the EU and the USA revealed that even limited fish consumption would lead to exceedance of these thresholds – possibly posing a challenge for risk communication.